2022
DOI: 10.1002/jcsm.12990
|View full text |Cite
|
Sign up to set email alerts
|

The ability of eight frailty instruments to identify adverse outcomes across different settings: the FRAILTOOLS project

Abstract: Background To compare the performance of eight frailty instruments to identify relevant adverse outcomes for older people across different settings over a 12 month follow-up. Methods Observational longitudinal prospective study of people aged 75 + years enrolled in different settings (acute geriatric wards, geriatric clinic, primary care clinics, and nursing homes) across five European cities. Frailty was assessed using the following: Frailty Phenotype, SHARE-FI, 5-item Frailty Trait Scale (FTS-5), 3-item FTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…The average reFI of the dataset was 0.21 which shows that this cohort is overall frail (mild frail 0.13 < reFI≤0.26), whereas other studies have also reported that RAC (nursing) home residents are known to be frail [ 8 ]. It should be noted that a 6-month history was selected based on the literature [ 33 , 34 , 37 40 ], but the history timeline could be reduced as per the needs and requirements of RACs for tracking purposes. This should be done with caution as a few frailty deficits are evaluated for their persistence over time such as polypharmacy (require a history of more than 2 weeks to avoid erroneous inclusion of antibiotics in polypharmacy), chronic pain (requires pain issues for consecutive 3 months [ 46 , 47 ]) and weight loss (weight loss within 6 months [ 33 , 48 ]).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The average reFI of the dataset was 0.21 which shows that this cohort is overall frail (mild frail 0.13 < reFI≤0.26), whereas other studies have also reported that RAC (nursing) home residents are known to be frail [ 8 ]. It should be noted that a 6-month history was selected based on the literature [ 33 , 34 , 37 40 ], but the history timeline could be reduced as per the needs and requirements of RACs for tracking purposes. This should be done with caution as a few frailty deficits are evaluated for their persistence over time such as polypharmacy (require a history of more than 2 weeks to avoid erroneous inclusion of antibiotics in polypharmacy), chronic pain (requires pain issues for consecutive 3 months [ 46 , 47 ]) and weight loss (weight loss within 6 months [ 33 , 48 ]).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…In the final reFI, eleven domains were identified that consisted of 32 frailty deficits or syndromes (Table 2 , further details are reported in Additional file 1 ). It should be noted that “ housebound ” and “ requirement for care ” deficits from Clegg’s list applied to all the residents at RACs i.e., residents in RACs are generally housebound and may require assistance for their daily routine work [ 33 , 34 ]. So “ requirement for care ” in terms of assistance was reflected in the selected frailty deficits for RACs, whose details are found in Additional file 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…FRAIL scale was coined since 2012 as an easy-to-administer instrument for identifying frail adults, and its results exhibited excellent correlation with those using the Fried's criteria [16] and other instruments [17]. Individuals with FRAIL-detected frailty (≥3 positive components) had an increased risk of mortality, disability, fall, institutionalization, and other geriatric syndrome development compared to robust ones [18][19][20]. FRAIL scale has been validated for its applicability in younger populations, including those with morbidities such as CKD or DM [21].…”
Section: Outcome Definitionmentioning
confidence: 99%